2023
DOI: 10.3389/fphar.2023.1131635
|View full text |Cite
|
Sign up to set email alerts
|

Fufang shenhua tablet, astragali radix and its active component astragaloside IV: Research progress on anti-inflammatory and immunomodulatory mechanisms in the kidney

Abstract: Background: Given the limited treatment options available for kidney disease, a significant number of patients turn to alternative therapies, including traditional Chinese medicine. Among these therapies, the Fufang Shenhua tablet (SHT) has garnered attention for its effectiveness in addressing the most common deficiency of Qi and Yin in chronic glomerulonephritis. Notably, the sovereign drug of SHT is Astragali Radix (AR), with the most abundant and effective component being Astragaloside IV (AS-IV). AS-IV ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The main component of XBF, Astragali Radix addresses immune-related conditions by modulating T-cell subsets (augmenting the quantity and function of CD4+ T-cells), boosting macrophage, natural killer cell, and lymphocyte activity, and regulating immune-related factors (such as IL-6, IL-10, IFN-γ, etc.) ( 81 ). 3-phenyl-propenal, extracted from Cinnamomi Ramulus, demonstrates immunomodulatory effects by suppressing TLR3, TLR4, and their downstream signalling components in Raw264.7 murine macrophages ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main component of XBF, Astragali Radix addresses immune-related conditions by modulating T-cell subsets (augmenting the quantity and function of CD4+ T-cells), boosting macrophage, natural killer cell, and lymphocyte activity, and regulating immune-related factors (such as IL-6, IL-10, IFN-γ, etc.) ( 81 ). 3-phenyl-propenal, extracted from Cinnamomi Ramulus, demonstrates immunomodulatory effects by suppressing TLR3, TLR4, and their downstream signalling components in Raw264.7 murine macrophages ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Huangqi-Danshen, a classic combination of CHM, exerts invigorating effects on qi, promotes blood circulation, and facilitates detoxification. A plethora of studies have revealed that both Huangqi and Danshen possess beneficial improvements on diverse diseases by inhibiting inflammatory response, reducing cell apoptosis, alleviating oxidative stress, and activating immunomodulation ( Ko et al, 2005 ; Qin et al, 2012 ; Shahrajabian et al, 2019 ; Li R. et al, 2023 ; Luo et al, 2023 ; Yang et al, 2023 ). Several components of Danshen have been reported to target NAD + metabolism for therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Astragalus, as a traditional Chinese medicine, has attracted much attention in tumor research for its multiple pharmacological effects [ 13 ]. Astragaloside IV, the most active compound in Astragalus, is associated with diverse pharmacological actions, including anti-inflammatory [ 14 ], antifibrotic [ 15 ], anticancer [ 16 ], and immune system regulation [ 17 ]. According to certain research, astragaloside IV has anticancer properties against a wide range of cancer types, such as liver cancer [ 18 ], stomach cancer [ 19 ], lung cancer [ 20 ], etc.…”
Section: Introductionmentioning
confidence: 99%